Assemblage of memory: on the structure, process and creativity in collective memory - Niziołek, Katarzyna (Creativity Studies, 2021)
The article is aimed at presenting and discussing the theoretical concept of assemblage of memory inspired by and grounded in the creative work done in connection with social research within the framework of participatory theatre. Based on three projects of this kind that I have collaborated on over the last couple of years, all taking memory as their theme, The Method of National Constellations (2014–2016), Prayer: A Common Theatre (2016–2017), and Bieżenki (2018), the concept draws both on artistic, and sociological thinking. An assemblage of memory could be roughly described as a product of creativity, which is constructed using “found” materials, such as stories, images, emotions, behaviours, objects, people even, to compose a new meaningful entity. This is congruent with what became to be known as the assemblage theory, started by Gilles Deleuze and Félix Guattari, who suggested that social phenomena, such as collective memory, one could add, should be viewed as dynamic and heterogeneous arrangements of a variety of elements, material and immaterial, natural and artificial, human and non-human, that are dependent on the connections between them rather than their intrinsic qualities. Thus, an assemblage of memory cannot be accessed through text-oriented methodologies that still seem to predominate the humanities (with its focus on the witness and testimony), but requires innovative, creative procedures, which, as exemplified by the above mentioned theatrical projects, are capable of revealing its structure and dynamics.